2016
DOI: 10.1016/j.jaci.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii subspecies–level dysbiosis in the human gut microbiome underlying atopic dermatitis

Abstract: The data suggest that feedback interactions between dysbiosis in F prausnitzii and dysregulation of gut epithelial inflammation might underlie the chronic progression of AD by resulting in impairment of the gut epithelial barrier, which ultimately leads to aberrant TH2-type immune responses to allergens in the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
283
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(331 citation statements)
references
References 56 publications
16
283
1
11
Order By: Relevance
“…In addition, the relation between the gut microbiome in inflammatory bowel disease and response to infliximab was also recently highlighted 90. In particular, when considering the reports about the role of the gut‐skin axis that might influence many diseases including the here investigated skin disorders 91, 92, 93.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the relation between the gut microbiome in inflammatory bowel disease and response to infliximab was also recently highlighted 90. In particular, when considering the reports about the role of the gut‐skin axis that might influence many diseases including the here investigated skin disorders 91, 92, 93.…”
Section: Discussionmentioning
confidence: 83%
“…4 Numerous investigators have shown that changes in the gut microbiota and intestinal inflammation have been associated with the development of allergic diseases. 6,8,13,23 The gut microbiota controls intestinal inflammation, which further modulates the development of the systemic immune system. 8,23 Altered gut microbiota induces epithelial damage resulting in increased intestinal inflammation, altered gut permeability and immunological balance, which affect the development of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,13,23 The gut microbiota controls intestinal inflammation, which further modulates the development of the systemic immune system. 8,23 Altered gut microbiota induces epithelial damage resulting in increased intestinal inflammation, altered gut permeability and immunological balance, which affect the development of allergic diseases. 8,13,23 The damaged epithelium with increased permeability might allow for the passage of allergens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations